Voorwoord and Professor Andrzej Borowski – Spiritus Litterarum Neerlandicorum Polonorum - Koch, Jerzy; Oczko, Piotr; Kiedroń, Stefan (Werkwinkel, 2015)
Professor Andrzej Borowski from the Jagiellonian University, whose 70th anniversary we celebrate this year, is a very well known scholar and literature historian, specialised in Old Polish Literature (Middle Ages, Renaissance and Baroque) - and with a background from Classical studies. A lesser known fact is that he also is a scholar active in the field of the Netherlandish (Dutch and Flemish) literature and culture: as author of numerous books and articles about (South) Netherlandish figures from the 16th and 17th century, as supervisor of numerous dissertations or habilitations in the field of the Netherlandish literature and as an inspiring personality in the field of the Netherlandish studies at Polish universities. He can indeed be seen as the Spiritus Litterarum Neerlandicorum in Poland.